Prienų šnektos žemutinių balsių kiekybė ir kiti skiriamieji bruožai - Jaroslavienė, Jurgita (Baltistica, 2006)
THE QUANTITY AND OTHER DISTINCTIVE FEATURES OF LOW VOWELS IN THE SUBDIALECT OF PRIENAIExperimental investigation of the quantity, quality and other distinctive features of the low non-short vowels in the subdialect of Prienai has shown that vowels of different origin are characterised by different acoustic and articulatory features. The measurement of vowel duration has indicated that [a˙]
Keywords: fonetika; kiekybė; Prienų šnekta